Implications of first language acquisition on English writing skills among learners with hearing impairment in special primary schools in Kericho County, Kenya - Mayeye, Teresa Otiu (Jooust, 2023)
English writing skills form a very important part of the English curriculum in primary schools in Kenya. English is taught in primary schools with an aim of enabling learners to acquire writing skills, which will in turn enable them to express their own ideas legibly and meaningfully and to communicate effectively in the language. Acquiring appropriate English writing skills poses a lot of challenges to learners with Hearing Impairment (HI). The purpose of this study was to explore the implications of first language (KSL) acquisition on English writing skills among learners with Hearing Impairment in special primary schools for the HI in Kericho County. The study was guided by the following objectives: to examine language discrepancies between KSL and English in writing skills, to establish the application of KSL when teaching English writing skills to learners with Hearing Impairment, to assess the strategies and methods employed when teaching and learning English writing skills among learners with HI and to determine the challenges faced by learners with HI in acquiring English writing skills. The study was informed by Noam Chomsky‟s theory of Universal Grammar of 1977. A multiple case study research design within a qualitative research approach was adopted. The units of analysis comprised 2 public primary schools for the HI in Kericho County. The study population comprised 48 informants (2 Curriculum Support Officers in charge of Special Needs Education drawn from each sub -County where the 2 special schools are located; 2 head teachers; 2 Heads of Language Department; 12 teachers of English; 3 parents with HI and 27 learners with HI in class 7). The sample of the study constituted 48 informants (100%) of the population. Purposive sampling technique was used to sample the 2 special primary schools for the HI while saturated sampling techniques was used to sample all Curriculum Support Officers for SNE, parents with HI, head teachers, Heads of Language Department, teachers of English and learners with HI in class 7. Data was collected using interview schedules, focus group discussions, observation checklist and document analysis guide. Validity and reliability of qualitative data was ascertained through Lincoln and Guba‟s (1985), qualitative paradigm approach. The qualitative data was analyzed thematically according to the themes of the research objectives. The study found out that there are discrepancies between KSL and English in writing skills in the aspects of plurals, sentence structure, punctuation, tenses, pronouns, use of adverbs/adjectives, use of auxiliary verbs, use of articles and conjunctions. The findings revealed that teachers of English used Kenyan Sign Language during English lessons which hampered acquisition of English writing skills. Discussions, guided writing, questioning and demonstration were the mostly used strategies, while use of teaching aids, ICT incorporation, peer teaching, cooperative teaching, group work and dramatization were the least used. The challenges that the hearing-impaired learners experienced include; vocabulary, use of the dictionary, use of figurative language and spellings. It was realized that the discrepancies between English and KSL had a great implication on English writing skills. It was concluded that more effort should be put on the use of Signed Exact English, use of the most appropriate strategies during English lessons and proper training on the use of the dictionary or acquisition of an online bilingual dictionary. The study recommended that teachers should use Signed Exact English in English lessons, teachers should use appropriate strategies when teaching English and lastly, the Government through the Ministry of Education to come up with an online bilingual (English-KSL) dictionary for learners with Hearing Impairment. It was suggested that a study should be done on how best to use L1 to facilitate proficiency in L2.
Keywords: First language acquisition on English writing skills; Learners with hearing impairment; learners with hearing impairment in special primary schools, Kenya